EMPOWERING DIGITAL BISNIS MITRA UMKM RUMAH BUMN BANDAR LAMPUNG - Appin purisky redaputri; Andoni Fornio Barusman; Hendri Dunan; Ahmad Cucus; Ayu Kartika Puspa (JURNAL CEMERLANG : Pengabdian pada Masyarakat, 2022)
Business activities are increasingly being carried out because they generate large profits. In marketing their products, business activities no longer require sellers to leave the house or rent shop outlets. Sellers just need to make good use of the E-commerce platform. E-commerce or commonly called Electronic Commerce is all forms of online buying and selling activities that can be accessed via the internet and various other electronic networks. There are lots of e-commerce used to promote sales, one of them is Tokopedia. Not only making sales easier, Marketplaces like Tokopedia have a great opportunity to grab the attention of consumers, because they offer free shipping and big discounts. Besides being able to save the budget, Tokopedia has full responsibility for the quality of its goods. Through the Empowering Digital Business for Rumah BUMN Partners which was held in the city of Bandar Lampung, Tokopedia collaborated with Rumah BUMN to enter the MSME community. The activity, which aims to make entrepreneurs equipped to face this competition, runs enthusiastically, as evidenced by the large number of MSMEs present.